Software implementation of 2 FA Software implementation of two-factor authentication to ensure security when accessing an information system (Journal of Mathematics Mechanics and Computer Science, 2019)
The article describes methods for applying two-factor authentication (2FA). An example of two-factor authentication using mobile devices as identifiers and the generation of a temporary password based on the hash function of encryption standards is considered. For an automated control system, a two-factor authentication model and a sequential algorithm for generating a temporary password using mathematical functions have been developed. Mathematical function is selected from the array of functions. To protect the opening of a one-time password, a secret string is read, consisting of a sequence of characters that will be generated randomly.Implemented software implementation on the Node.js software platform using the JavaScript programming language, as well as frameworks and connected system libraries. A document-based database management system with open source MongoDB, using for storing and processing information. The analysis of the software implementation of the proposed algorithm.
Keywords: two-factor authentication; data security; one-time password (OTP) generation; security methods; mobile application; smartphone